The role of strategic memory in the successful use of the COSO model for auditing human resource management - Hussein, Hussein Waleed; khamees, Luma hadi (Journal of Economics and Administrative Sciences, 2021)
The main purpose of the research is to diagnose the importance of the role that strategic memory plays with its three variables (content, structure, and processes) in helping the human resource department to use the COSO model with its five components (culture and governance, strategy and objectives, performance, communications and information, and feedback) in auditing activities and tasks Her own. As the research problem emphasized the existence of a lack of cognitive perception, of the importance of strategic memory, and the investment of its components in the rationalization of the application of the COSO model. and therefore it can be emphasized that the importance of the research is to provide treatments for problems related to the variables that have been studied within the research organization. As for the objectives of the research, they are represented by conducting a descriptive analysis of the investigated variables and tests of the relationship between them. To achieve the objectives of the research, use the descriptive-analytical approach. As the questionnaire was built using international indicators and standards, and it was distributed to a sample consisting of (97) members of the staff of Al-Rafidain University College. The researchers relied on some statistical tools available in the statistical program (SPSS-V23) in order to enter and process data, and the results confirmed the validity of the main and sub-research hypotheses. Accordingly, the researchers recommended the necessity of preparing all the requirements necessary to build strategic memory and then employing it in providing the human resources department with information that enables it to apply the COSO model in auditing its activities